Tensile Strength of Packaging Materials Made of Rice Fiber with Gondorukem Coating - Caturwati, Ni Ketut; Pinem, Mekro Permana; Visoka, Cri Kalki (Universitas Sultan Ageng Tirtayasa, 2025)
Packaging is one of the important needs in the food business that is difficult to avoid. Developing packaging products for food is an important thing that must be done to maintain cleanliness, health and the environment. Packaging waste that uses plastic as the basic material causes environmental pollution because it is not easily decomposed. Green packaging is one form of packaging that uses environmentally friendly materials such as rice straw. Bio-foam from straw combined with PVA, Glycerin, corn starch and distilled water is made into sheets for packaging. This sheet is tested with the addition of a coating derived from gondorukem which comes from plants. With this coating, it is expected to increase the tensile strength and hydrophobicity of the material surface. Testing was carried out with variations in the mixture of gondorukem and alcohol as the basic coating material, namely gondorukem concentrations of 20%, 40% and 60%. The tensile test results showed that a coating with a concentration of 60% gondorukem produced the highest tensile strength value. The increase in tensile strength reached 102% of the tensile strength of the sheet without gondorukem coating.